2020
DOI: 10.1038/s41598-019-57180-6
|View full text |Cite
|
Sign up to set email alerts
|

Changes in left ventricular blood flow during diastole due to differences in chamber size in healthy dogs

Abstract: Vorticity is a novel index that reflects diastolic function of left ventricle. The size of the ventricle can influence the ventricular diastolic blood flow. We evaluated effect of ventricular size on diastolic function and diastolic intracardiac blood flow using a particular species of dogs, which has a wide range of body size. Vector flow mapping was used for evaluation of intracardiac blood flow, and intraventricular pressure gradient (IVPG) was used for evaluation of diastolic function. 58 dogs weighing 1.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 20 publications
(23 reference statements)
2
27
0
Order By: Relevance
“…This point may be covered by DXR overdosing, but it would not be clinically approved. The number of dogs was also relatively small, but the normality of the produced data was acceptable, and our team showed good repeatability of the used techniques [ 11 ]. Besides, we did not study the changes in IVPG under anesthesia since a stable hemodynamic condition was followed in the used protocol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This point may be covered by DXR overdosing, but it would not be clinically approved. The number of dogs was also relatively small, but the normality of the produced data was acceptable, and our team showed good repeatability of the used techniques [ 11 ]. Besides, we did not study the changes in IVPG under anesthesia since a stable hemodynamic condition was followed in the used protocol.…”
Section: Discussionmentioning
confidence: 99%
“…IVPD is obtained from color M-mode echocardiographic (CMME) images using Euler's equation [10]. The intraventricular pressure gradient (IVPG) can be calculated by dividing the IVPD by the length of the left ventricle (LV); consequently, unlike the IVPD, IVPG is not affected by the size of the heart [11][12][13]. Generally, the length of the LV, from the mitral valve to the apex, is divided into basal, mid, and apical parts, and each has its corresponding IVPG index.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of an accessory lung right lobe that partially obscuring the heart, gas-filled rumen against the diaphragm, the vertical orientation of the heart, and a large and thick sternum are the main obstacles to obtain good quality images during echocardiography in sheep and goats [35][36][37]. Our research group is qualified in the repetitive echocardiography of small animals as well as goats [23,38]. In the current study, a slight elevation of the animal from its back on the echocardiographic stand with proper orientation of the transducer was required sometimes for better alignment to measure the mitral inflow, aortic flow as well as the TDI from the left apical view.…”
Section: Discussionmentioning
confidence: 99%
“…IVPD obtained by CMME is considered a sensitive indicator of diastolic function [6] and has the advantage of repeatability, unlike invasive catheterization. Similarly, the IVPG exerts the same properties as IVPD without being affected by the LV length [8][9][10][11]. Generally, the length of the LV, from the mitral valve to the apex, is divided into basal, mid, and apical parts, and each part has its corresponding IVPD and IVPG indices and a defined role in the diagnosis of cardiac dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the length of the LV, from the mitral valve to the apex, is divided into basal, mid, and apical parts, and each part has its corresponding IVPD and IVPG indices and a defined role in the diagnosis of cardiac dysfunction. For instance, it was reported that basal IVPD increases when congestion progresses, whereas mid IVPD decreases when diastolic dysfunction progresses [8,12]. Mid-to-apical IVPG was found to reflect the active relaxation of the LV during diastole, whereas the apical IVPG plays the main role in actively sucking the blood into the ventricle [13,14].…”
Section: Introductionmentioning
confidence: 99%